Commission 37: Star Clusters and Associations - Elmegreen, Bruce; Carraro, Giovanni; Hatzidimitriou, Despina; Da Costa, Gary; de Grijs, Richard; Deng, LiCai; Lada, Charles; Lee, Young-Wook; Minniti, Dante; Sarajedini, Ata; Tosi, Monica (2012)
Research on star clusters and associations includes the observation and theory of stellar groupings as they form and evolve, cluster disruption, stellar interactions inside clusters, and star formation in dense environments. In what follows, we list past, present and future meetings (http://www2.cadc-ccda.hia-iha.nrc-cnrc.gc.ca/meetings/), publications statistics and important surveys, reviews, and databases about clusters.